The profiles of first and second SARS-CoV-2 waves in the top ten COVID-19 affected countries - Jyoti Chhibber-Goel; Sumit Malhotra; N.M. Anoop Krishnan; Amit Sharma (Inishmore Laser Scientific Publishing Ltd, 2021)
In March 2020, the World Health Organization (WHO) acknowledged the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) as a "*public health emergency of international concern*." Within a month, coronavirus disease 2019 (COVID-19) was declared a pandemic. As of 21 July 2021, 192.8 million cases and 4.13 million deaths have been attributed to COVID-19 worldwide. Here we discuss the data from top ten COVID-19 affected countries, with an emphasis on the average strolling period of 6 to 8 months between first and second wave in these nations. Our study ascertains that analysis of the data from countries temporally ahead of others during the pandemic gives policymakers the chance to strategize and postpone or mitigate subsequent COVID-19 waves. With governments throughout the globe continuing their immunisation efforts, a study of the key indicators of COVID-19 waves from the top ten countries is critical to preparing the healthcare system to save millions of lives.